FEM Analysis and Experimental Validation of Friction Welding Process of 6xxx Alloys for the Prediction of Welding Quality. (2015) - Donati, Lorenzo; Troiani, Enrico; Proli, Paolo; Tomesani, Luca
Abstract: In the paper the Friction Welding (FRW) process is investigated by means of FEM simulation and experimental trials on AA 6082-T6 round extruded bars. Tests are realized at different rotational speeds and forging forces: the thermal field is monitored by means of k-type contact thermocouples and a contactless self-calibrating pyrometer. Deform lagrangian code is initially validated and optimized for process simulation of experimental trials then the simulations were used for the analysis of welding quality (through welding criteria) and for the microstructure evolution by means of a model already developed by the authors for aluminum extrusion microstructure evolution prediction.